A STUDY CONCERNING THE DEVELOPMENT OF SPEED THROUGH THE USE OF DYNAMIC GAMES IN FOOTBALL, JUNIORS OF 14 TO 15 YEARS OLD - ROZSNYAI, Radu Adrian; MONEA, Dan; RADU, Paul Ovidiu (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2017)
The authors of this paper have attempted to find an optimum ratio between the actual training and game implementation in the process of multilateral development of the football player, emphasizing the development of speed throughout games both specific and nonspecific to football. Due to the fact that the dynamic games create a state of emulation, doubled with a high energy consumption, they also have an educational and multilateral formative influence on children, especially if they are correctly selected and conducted, so as to satisfy the children’s variety of interests and development needs. Therefore, it is highly recommended the alternative use of games in sports training (Epuran, 2001). In this study, the authors have intended to show that through certain ways, methodical procedures and adequate systems of action, all applied differently and collectively in the sports training, games help to develop speed in all its forms. Objectives: The aims were to prove that games can help the development of speed and a physical progress can be obtained for football players as a result of applying games in sports training. Materials and methods: To properly conduct the experiment, the following materials were used: 2 stopwatches, an object used to signal the start (a starter), stakes and a colourful spray to draw lines. Conclusions and recommendations: Introducing games in the sports training brings many advantages in training sports people, the results of speed tests being better and as a result of this, the psychological positive effect on the player’s mood is highly enhanced; therefore, our future recommendation is that football coaches and others, should use and implement games when training sportspeople. REZUMAT. Studiu privind dezvoltarea vitezei prin utilizarea jocurilor dinamice in fotbal la juniori cu vârsta cuprinsă între 14-15 ani. Autorii acestei lucrări vizează găsirea unui raport optim între antrenamentul propriu-zis și implementarea jocului în procesul de dezvoltare multilaterală a jucătorului de fotbal, punând accentul pe dezvoltarea vitezei prin jocuri specifice și nespecifice jocului de fotbal. Datorită faptului că jocurile dinamice creează o stare de emulație, dublată de un consum energetic mare și în același timp au o influență educativă și formativă multilaterală asupra copiilor dacă sunt corect selecționate și dirijate, astfel încât să satisfacă varietatea intereselor și nevoilor de creștere și dezvoltare a acestora, se recomandă folosirea alternativă a jocurilor în antrenamentul sportiv (Epuran, 2001). Prin acest studiu autorii și-au propus să arate că jocul prin anumite modalități, procedee metodice și sisteme de acționare adecvate, aplicate în mod diferențiat și colectiv în antrenament sportiv, ajută la dezvoltarea vitezei sub toate formele ei. Obiective: Obiectivele au fost acelea de a demonstra că jocul ajută la dezvoltarea vitezei și se poate obține un progres fizic al jucătorilor de fotbal prin aplicarea acestora în antrenamentul sportiv. Materiale și metode: Pentru desfășurarea experimentului s-au folosit următoarele materiale: 2 cronometre, un obiect pentru declanșarea sunetului la start (starter), jaloane și un spray colorat pentru a trasa linii. Concluzii și recomandări: Apariția jocurilor în antrenamentul sportiv aduce un plus în pregătirea sportivilor, rezultatele probelor specifice vitezei fiind mai bune, iar prin valența lor, jocurile au și un efect psihic pozitiv asupra stării de spirit al jucătorului; recomandăm ca pe viitor, antrenorii de fotbal, și nu numai, să implementeze jocul în pregătirea sportivilor. Cuvinte cheie: jocuri dinamice, fotbal, dezvoltarea vitezei.